High compression algorithm for digital image components - Колесникова, Татьяна Анатольевна; Новикова, Юлия Сергеевна (Eastern-European Journal of Enterprise Technologies, 2012)
The article deals with the compression of high-frequency components of the digital image based on the M-sequence. The compression algorithm halftone images without loss of information is suggested